Optimization of localized photothermal therapy utilizing liposomal formulation of IR-820 photoactive dye - Dinesh Shrestha; Viswanathan Sundaram; Shoukath Sulthana; Danyel Manteufel; Shelby Metcalf; Santosh Aryal (Heliyon)
Current phototherapeutic approaches in cancer treatment include photothermal (PTT) and photodynamic (PDT) therapy, which harness light energy for the activation of a photoactive molecule resulting in the destruction of cancer cells. In PTT, generated local heat kills abnormal cells; whereas, in PDT, a series of biochemical reactions generating reactive oxygen species is responsible for cellular damage. However, a major concern arises in the cellular delivery of an optimal amount of a photoactive molecule required for the desired effect. In this work, we employed IR-820, a new Indocyanine green dye, in a liposomal formulation to maximize its delivery to cancer cells while minimizing its adverse side effects for localized PTT. The synthesized liposomes were monodispersed and highly stable with a hydrodynamic size of 120 ± 5 nm and a narrow polydispersity index of 0.15 ± 0.02. The optimized liposome loaded with IR-820 showed gradual and sustained release in acidic and physiological pH conditions, and these liposomes exhibited biocompatibility when treated with human breast cancer cells (MCF-7). Also, this formulation showed immune response when compared to free IR-820 upon treatment to THP1 monocyte cells by regulating TNF-α and IL-6 cytokines. Irradiation of free IR-820 and liposomal IR-820 aqueous solutions using an 808 nm near-infrared laser resulted in a rapid rise in temperature up to 60 °C within 30 s, as captured with a FLIR infrared camera. Such an order of magnitude of temperature rise effectively destroys more than 50 % of human breast cancer cells (MCF-7) within 30 s of NIR laser irradiation. Considering the ease of liposome fabrication and observed phototoxicity, the proposed liposomal formulation of IR-820 photoactive dye could have great potential and hold promise in photothermal therapy of cancers.